"Whistleblowing": a health issue. Issue 6905 (11th September 1993) - Lennane, K J
Abstract : OBJECTIVE–To examine the response of organizations to "whistleblowing" and the effects on individual whistleblowers. DESIGN–Questionnaire survey of whistleblowers who contacted Whistleblowers Australia after its publicity campaign. SETTING–Australia. SUBJECTS–25 men and 10 women from various occupations who had exposed corruption or danger to the public, or both, from a few months to over 20 years before. RESULTS–All subjects in this non-random sample had suffered adverse consequences. For 29 victimization had started immediately after their first, internal, complaint. Only 17 approached the media. Victimization at work was extensive: dismissal (eight subjects), demotion (10), and resignation or early retirement because of ill health related to victimization (10) were common. Only 10 had a full time job. Long term relationships broke up in seven cases, and 60 of the 77 children of 30 subjects were adversely affected. Twenty nine subjects had a mean of 5.3 stress related symptoms initially, with a mean of 3.6 still present. Fifteen were prescribed long term treatment with drugs which they had not been prescribed before. Seventeen had considered suicide. Income had been reduced by three quarters or more for 14 subjects. Total financial loss was estimated in hundreds of thousands of Australian dollars in 17. Whistleblowers received little or no help from statutory authorities and only a modest amount from workmates. In most cases the corruption and malpractice continued unchanged. CONCLUSION–Although whistleblowing is important in protecting society, the typical organisational response causes severe and longlasting health, financial, and personal problems for whistleblowers and their families.